The quorum sensing system of Yersinia enterocolitica 8081 regulates swimming motility, host cell attachment, and virulence plasmid maintenance - Ng, Yen-Kuan; Grasso, Marco; Wright, Victoria; Garcia, Vanina; Williams, Paul; Atkinson, Steve (MDPI, 2018)
Although Yersinia enterocolitica genomes are highly heterogeneous, they contain a conserved N-acylhomoserine lactone-dependent (AHL) quorum sensing (QS) system consisting of the luxR and luxI orthologs yenR and yenI respectively. Certain hypervirulent strains also contain a putative orphan luxR gene, ycoR, that is not linked to an AHL synthase. To explore the contribution of yenR/yenI/ycoR to QS-dependent phenotypes in Yersinia enterocolitica strain 8081, single and multiple mutants were constructed. AHL profiling identified N-(3-oxohexanoyl) homoserine lactone, N-hexanoylhomoserine lactone, and N-(3-oxoseptanoyl) homoserine lactone as the most abundant. The AHL profiles of the yenR, ycoR and yenR/ycoR mutants were similar to the parent suggesting that the two LuxR homologues do not regulate AHL production while the yenI mutants were AHL-negative. A role for QS in swimming motility and cell attachment was demonstrated. Down-regulation of the virulence plasmid partition gene, spyA, in yenI and yenI/yenR/ycoR mutants is consistent with the greater loss of the Y. enterocolitica pYVe virulence plasmid in the yenI mutant during serial passage at 37 C but not at 22 C. A role for QS-regulated spyA in virulence plasmid maintenance is suggested.